2017
DOI: 10.1002/art.40226
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intravenous Golimumab in Patients With Active Psoriatic Arthritis

Abstract: ObjectiveTo evaluate the safety and efficacy of intravenous (IV) golimumab treatment in psoriatic arthritis (PsA).MethodsIn this phase III, randomized, double‐blind, placebo‐controlled trial, patients were randomly assigned to receive IV placebo (n = 239) or golimumab at 2 mg/kg (n = 241) at weeks 0, 4, 12, and 20. The primary end point was the proportion of patients meeting the American College of Rheumatology 20% improvement criteria (achieving an ACR20 response) at week 14. Controlled secondary end points i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 24 publications
5
114
0
Order By: Relevance
“…The fully human anti-TNFα monoclonal antibody golimumab has demonstrated long-term clinical efficacy and inhibition of structural damage in patients with moderate-to-severe PsA [7][8][9][10]. Given the importance of assessing the diverse manifestations in patients with PsA [5], we conducted post hoc analyses to assess changes in radiographic progression in patients with varying levels of composite index-defined disease activity following treatment with IV golimumab or placebo in the large phase 3 GO-VIBRANT PsA trial [9,10]. Composite endpoints were chosen for these analyses because they allow the assessment of multiple clinical manifestations in a single instrument [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The fully human anti-TNFα monoclonal antibody golimumab has demonstrated long-term clinical efficacy and inhibition of structural damage in patients with moderate-to-severe PsA [7][8][9][10]. Given the importance of assessing the diverse manifestations in patients with PsA [5], we conducted post hoc analyses to assess changes in radiographic progression in patients with varying levels of composite index-defined disease activity following treatment with IV golimumab or placebo in the large phase 3 GO-VIBRANT PsA trial [9,10]. Composite endpoints were chosen for these analyses because they allow the assessment of multiple clinical manifestations in a single instrument [21].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the GO-VIBRANT study design and participant eligibility criteria have been reported [9,10]. Briefly, eligible patients were bio-naïve, had PsA based on the ClASsification of Psoriatic ARthritis (CASPAR) criteria [11] for ≥ 6 months, and demonstrated active disease (swollen joint count [SJC] ≥ 5 and tender joint count [TJC] ≥ 5 at screening and baseline and screening Creactive protein [CRP] ≥ 0.6 mg/dL), despite therapy with disease-modifying antirheumatic drugs (≥ 3 months) and/or nonsteroidal anti-inflammatory drugs (≥ 4 weeks) or an intolerance to these therapies.…”
Section: Patients and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In the phase III GO‐VIBRANT study (A Multicenter, Randomized, Double‐Blind, Placebo‐Controlled Trial of Golimumab, an Anti‐TNFα Monoclonal Antibody, Administered Intravenously, in Subjects With Active Psoriatic Arthritis), adult patients with active PsA showed greater improvements in the signs and symptoms of PsA and less radiographic progression through week 24 when receiving intravenous (IV) golimumab compared with those who received placebo . Improvements in health‐related quality of life (HRQoL) were also greater for patients in the golimumab group . Adverse events (AEs) through week 24 were consistent with the known safety profile of IV golimumab.…”
Section: Introductionmentioning
confidence: 99%